Gender differences in Obeying Traffic Regulations and the Related Cognitive Factors among Elementary School Students in Khorramabad City: Application of Health Belief Model - Maryam ghavami; Tayebeh Fasihi Harandy; Kourosh kabir; Saeed Saadatmand (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective:  Vehicles are one of the most common causes of accidents among school students. Therefore, this research was conducted to determine the gender differences in obeying traffic regulations and the related cognitive factors among elementary school students in Khorramabad City, Iran. Materials and methods: This was a descriptive and correlational comparative study. 360 elementary school students in Khorramabad City in the year 2014-2015 were selected through multistage sampling method which answered the demographic questionnaire and questions related to health belief model (HBM) structures and behaviors. The data were analyzed using SPSS20 through Pearson Correlation, Stepwise Regression, Wilk's Lambda and multivariate analysis of variance (MANOVA) tests. Results: Perceived self-efficacy, perceived barriers and perceived benefits could predict 21.4% of the changes related to the variable of obeying traffic regulations. Meanwhile, there was a statistically significant difference among female and male students in HBM structures and behavior. Conclusion: Male students were less informed of HBM structures and behavior compared to female students. Thus, it is necessary to use HBM-based teaching to promote safety culture among students (especially male students). Paper Type: Research Article.